Development of new product - Karničar Šenk, Mateja (Organizacija (Kranj), 2010)
The result of our research is a developed and implemented set of activities for new process or product development (NPD procedure) for SMEs environment in the plastic processing industry, which enables the production of products and services with a high value added. The developed NPD procedure consists of five consecutive and overlapping steps: attracting orders, designing a project, developing a product, developing a process and zero production series. Each distinct step is further divided into sub-activities supported by adequate methods and managed in an information system. Investigated and included were three different methodologies use for NPD procedure in the automotive industry such as Advanced Product Quality Planning (APQP), Design for Six Sigma (DFSS) and Stage/Gate methodology. The results presented in the paper show that the developed NPD procedure significantly improved NPD in terms of cost management and time-effectiveness.
Keywords: mala podjetja; management; srednja podjetja; industrijski izdelki; proizvodi; razvoj; postopki; skupinsko delo; kvaliteta; organizacija; organization